2019
DOI: 10.1029/2019gl081910
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Pumping Impacts Onshore Groundwater Resources and Land Subsidence

Abstract: Freshened groundwater exists offshore along many coastlines worldwide. Pumping of these offshore resources has been proposed for more efficient oil production as well as drinking and agriculture. Although pumping can occur tens to hundreds of kilometers offshore, these activities may threaten connected onshore aquifer systems. We conducted numerical simulations of variable‐density groundwater flow and salt transport in coastal aquifers with different geologic structure subject to offshore pumping to assess pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…7a-c). The relatively short distances of observed OFG, in comparison to prior studies 48 , are due to a lateral decrease of permeability offshore ( Supplementary Fig. 5b).…”
Section: Resultsmentioning
confidence: 48%
“…7a-c). The relatively short distances of observed OFG, in comparison to prior studies 48 , are due to a lateral decrease of permeability offshore ( Supplementary Fig. 5b).…”
Section: Resultsmentioning
confidence: 48%
“…This assumption is reasonable when the considered offshore submarine aquifer is far enough from the coastline. There are even many offshore freshwater submarine aquifers extending in all horizontal directions extensively and very far from the coastline [22][23][24][25][26]. In addition, several existing analytical studies assume that the coastal aquifer systems extend seaward infinitely (e.g., [10,14,17,27]).…”
Section: Mathematical Model and Analytical Solutionmentioning
confidence: 99%
“…Although there are some analytical solutions of tide-induced groundwater fluctuations in the submarine confined aquifer system in the offshore part (e.g., [14,17,18]), the dependency of the tide-induced groundwater head fluctuation in the offshore submarine aquifer on the model parameter was not analyzed or discussed. The offshore submarine aquifers are important both in water resources and in marine environments (e.g., [21][22][23][24][25][26]). Therefore, the study of the groundwater flow in offshore submarine aquifer systems is necessary and important.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pumping these offshore fresh water reserves should not be considered as "mining" in the negative sense and could on the contrary even lead to reducing the current negative effects of onshore groundwater pumping (Kooi and Groen, 2001). However, the study by Yu and Michael (2019) found that offshore pumping could potentially impact the onshore land subsidence rates and submarine groundwater discharge depending on geological complexity. Hence, a need exists for better understanding of coastal geological heterogeneity when assessing OFGVs for potential exploitation, and to secure that such is not harmfully impacting hydrogeological conditions in the adjacent onshore.…”
Section: Introductionmentioning
confidence: 99%
“…These can be largely reduced by using fresh or slightly brackish water (i.e., OFGV) as feedwater to desalination plants and thus cutting down the brine output and energy costs (Ghaffour et al, 2013). Moreover, OFGV could supply low-cost water in areas with offshore oil production activities (Yu and Michael, 2019). This adds to the urgency of better understanding and quantifying the OFGV occurrence before these can be successfully mined for human consumption.…”
Section: Introductionmentioning
confidence: 99%